PRESERVING HUMAN VALUES WITHIN MINANGKABAU CHILDREN ORAL STORIES THROUGH CREATIVE INDUSTRY (MELESTARIKAN NILAI-NILAI KEMANUSIAAN DALAM CERITA LISAN ANAK MINANGKABAU MELALUI INDUSTRI KREATIF) - Toti Sri Mulyati; Satya Gayatri; Yuhandri Yuhandri (Jurnal Gramatika, 2020)
Minangkabau is a territory situated in West Sumatra Indonesia. The history of Minangkabau comes from an oral tradition which is then written and known as "Tambo". Many oral stories that appear in Minangkabau contain human values, for example the story of Malin Kundang which gives human values to be obedient to parents. Through this research, oral stories were collected from informants and written in the form of illustrated books. This study specifically collects children oral stories of Minangkabau, then analyzed, and made into a illustrated story book, because it is feared that these oral stories would disappear along with the death of the informants. These stories are written in the Minang language so that the young generation and children will keep maintaining and understanding the Minang language in daily life. Through the creative industry, oral stories are packaged into illustrated story books in Minang language. The benefit is that Minang children who live in Minang or beyond its areas will hopefully understand and can use the Minang language properly. The approach used in this research is the folklore approach by collecting stories spoken in the Minangkabau community that have not been written yet.